Outage probability analysis of DF PSR energy harvesting full-duplex relaying network with presence of the direct link using MRC technique - Van-Duc Phan; Phu Tran Tin; Minh Tran; Tran Thanh Trang (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In the last time, the system performance of the energy harvesting relay network has been considered in many studies. In this paper, we propose and investigate the outage probability (OP) of the Decode-and-Forward (DF) Energy Harvesting (EH) Full-Duplex (FD) Relaying network in Power Splitting Protocol (PS) using MRC Technique with the presence of the direct link. In the first stage, the integral form of the OP is derived in two cases with and without the presence of the direct link. After that, we analyze the influence of main system parameters on the OP and comparison between two cases with and without the presence of the direct link. Finally, the results show that all simulation and analytical results match well with each other based on the Monte Carlo verification simulation.